Floristic Diversity of the Natural Forests of Dimbokro Region, Centre-Eastern Côte d’Ivoire - Rita, Biagné Massa; François, Kouamé N’Guessan; Edouard, N'Guessan Kouakou (European Scientific Journal, ESJ, 2018)
This study, carried out in three types of forest types (reserve, riparian and of plateaus) in a savannah and forest mosaic region of Côte d’Ivoire, aims to arise up the floristical characteristics of these natural forests. Trees and lianas with DBH≥10 cm were sampled into 30 plots of 50mx20m per forest type and named botanically. The floristic diversity and taxa distribution were analyzed using various coefficients and a Factorial Correspondence Analysis respectively. We found 89 species belonging to 77 genera and 36 families. The most abundant taxa were Verbenaceae family (43%), LeguminosaeCaesalpinioideae subfamily (19%), Leguminosae-Mimosoideae subfamily (6%), Malvaceae family (6%), Sapotaceae family (6%), Moraceae family (4%) and Leguminosae-Papilionoideae subfamily (3%). Both riparian forests and forests of plateaus showed higher species richness and diversity and were similar for these parameters. Average species richness varied from 5 in forest reserve to 9 in both riparian forests and forests of plateaus respectively. Shannon-Weaner’s diversity index was set between 0.832 in the forest reserves and 1.723 in the riparian forests while the equitability index of Pielou varied from 0.516 in the forest reserves to 0.789 in the riparian forests. The forest reserves and of plateaus showed similar spatial distribution of the woody plants with DBH ≥ 10 cm.